PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA UD. CAHAYA SABLON TELUKDALAM KABUPATEN NIAS SELATAN - Magdalena Fitri Bohalima (Jurnal Ilmiah Mahasiswa Nias Selatan, 2022)
The background of the problem in this research is that there are still consumers who complain about the quality of products owned by UD. Screen printing light, there is an error in printing the letters on the screen, there is an error in placing the color of the letters on the screen, there is an error in placing the color of the letters on screen printing and the durability is still low. The purpose of this study was to determine the effect of product quality on consumer purchasing decisions at UD. Telukdalam Screen Printing Light, South Nias Regency. This type of research used is quantitative research. The data source is the consumer. The population and sample used are 45 respondents. The data collection technique or instrument used in this study is by distributing questionnaires directly to consumers. The data analysis method used is simple linear regression analysis. The results of this study indicate that product quality (X) has a positive and significant effect on consumer purchasing decisions at UD. Telukdalam Screen Printing Light, South Nias Regency with a tcount of 3.286 > ttable of 2.017 with df, n-k-1 (45-1-1) = 43